Pendampingan Guru-Guru SD Krapyak Wetan dalam Menerapkan Pembelajaran Tematik dengan Pendekatan STEM - Richardo, Rino; Eliana, Hasna Ulayya; Anisah, Nela Khoridatul; Aisyah, Nabila Aqidatul; Halimatussa’diyah (Jurnal Pemberdayaan Masyarakat, 2021)
The ability of teachers in designing thematic learning that can increase the activities of elementary school students to develop sanins and mathematics literacy is still not optimal. So this has implications for the low ability of scientific and mathematical literacy as well as student activity. So that the purpose of this service is to increase the knowledge and skills of teachers in developing STEM-based learning innovations. This is because STEM is an approach that combines elements of science and mathematics in learning, and learning is designed to develop projects so that students can be active in learning. This service is a grant from the Program Kreativitas Mahasiswa (PKM) in 2020. The method of implementing this service has been carried out in several stages including planning, namely (1) initial coordination with the school, preparation of learning tools, and team strengthening; (2) implementation, namely the implementation team delivering training materials to teachers, practicing knowing student activities in STEM learning, and teachers practicing STEM learning to students; and (3) Evaluation. All stages of the method are carried out online. This service program produces a STEM learning activity guide book which contains STEM learning activity material that has been adapted to mathematics and science material for grades 4,5 and 6 SD. so that it can be used as a continuation of these activities. In addition, the increase in the ability of teachers in STEM learning is shown by increasing students' understanding of the material presented through the given test questions.